Theoretical and methodological basis of researching the essence of international tourism - Mozolev, O. (Journal of Education, Health and Sport, 2024)
The article analyzes the theoretical and methodological foundations for studying the essence of international tourism. Considering the category “international tourism”, it has been established that it has characteristic features that distinguish it from other types of tourism. One of them is the crossing of state cordons, which is associated with the most important formalities: registration of foreign passports and visas, completion of military procedures, currency and medical control. We have identified the main features of international tourism: systematic development, sensitivity to market changes, steady changes in the supply and position of tourist services, an increase in the range of these services. International tourism is an important stimulus for the development of world trade, which leads to increased activation of international trade exchanges. Nowadays, international tourism is viewed as an independent type of international connections. Without regional cooperation, international tourism cannot develop successfully. International tourism is a rich phenomenon that combines economic, social, cultural and environmental aspects. It has an inexhaustible potential for sustainable development, and it has connections with the rich wealth of the economy, which implies a new place in the socio-economic life of countries and peoples. International tourism has the potential to integrate, consolidate, embrace constructive dialogue, solidarity and mutual understanding between peoples. Thus, international tourism is an influx channel of “public diplomacy”.